The role of soluble tumor necrosis factor receptor type I in tumor survival - Selinsky, Cheryl Lynn, author; Howell, Mark, advisor (Colorado State University. Libraries, 1999)
Direct lysis of tumor cells by tumor necrosis factor (TNF) is an important mechanism of anti-tumor immunity. Nevertheless, tumors often persist in mammalian hosts despite significantly elevated serum levels of TNF. One possible explanation for this paradox is that corresponding increases in the levels of soluble tumor necrosis factor receptor type I (sTNFRI), a potent inhibitor of TNF, interfere with TNF-mediated tumor elimination. To formally evaluate the ability of sTNFRI to inhibit antitumor mechanisms, we have engineered sTNFRI production into the TNF-sensitive murine cell line, L929. In in vitro analyses, sTNFRI-secreting L929 cells displayed increased resistance to direct lysis by TNF, and to LAK cell- and CTL-mediated cellular cytolysis when compared to the parental cell line which does not secrete sTNFRI. These landings suggest that, in vivo, sTNFRI may contribute to tumor development and persistence. A formal role for sTNFRI in tumor survival was demonstrated by comparing the growth of sTNFRI-secreting L929 cells with that of the unmodified parental fibrosarcoma cell line in an in vivo mouse transplantation model. L929 cells are non-tumorigenic in syngeneic recipients, yet they produce fibrosarcomas in sub-lethally irradiated animals, indicating that tumor growth in unirradiated animals is prevented by immunological mechanisms. The secretion of sTNFRI by L929 cells, however, markedly enhanced their tumorigenicity in irradiated, as well as immunocompetent, recipients. Immunization with sTNFRI to induce antibodies which neutralize the binding of sTNFRI to TNF abrogated this tumorigenicity. Collectively, these data formally demonstrate that sTNFRI directly influences tumor growth and persistence in vivo, and they justify the development of methods to selectively inactivate sTNFRI in the circulation of tumor-bearing hosts. Toward this end, we have produced monoclonal antibodies that neutralize the binding of sTNFRI to TNF and have tested their efficacy in our mouse transplantation model.
Keywords: immunology; oncology